2021
DOI: 10.1172/jci.insight.142189
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of epithelial DUOX1 in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease characterized by small airway remodeling and alveolar emphysema due to environmental stresses such as cigarette smoking (CS). Oxidative stress is commonly implicated in COPD pathology, but recent findings suggest that one oxidant-producing NADPH oxidase homolog, dual oxidase 1 (DUOX1), is downregulated in the airways of patients with COPD. We evaluated lung tissue sections from patients with COPD for small airway epithelial DUOX1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…It is important to note that such associations in humans may also be impacted by exposure history (such as smoking), and lung epithelial DUOX1 was indeed found to be suppressed in smokers compared with nonsmokers (89). Moreover, we recently reported that airway DUOX1 protein levels are downregulated in small airways of patients with advanced (stage IV) COPD relative to age-matched non-COPD control subjects, which may be linked with altered smoking status and/or history (33). In these studies, we also observed that DUOX1 downregulation correlated significantly with loss of lung function and that DUOX1-deficiency worsened experimentally induced emphysema in mice (33).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is important to note that such associations in humans may also be impacted by exposure history (such as smoking), and lung epithelial DUOX1 was indeed found to be suppressed in smokers compared with nonsmokers (89). Moreover, we recently reported that airway DUOX1 protein levels are downregulated in small airways of patients with advanced (stage IV) COPD relative to age-matched non-COPD control subjects, which may be linked with altered smoking status and/or history (33). In these studies, we also observed that DUOX1 downregulation correlated significantly with loss of lung function and that DUOX1-deficiency worsened experimentally induced emphysema in mice (33).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we recently reported that airway DUOX1 protein levels are downregulated in small airways of patients with advanced (stage IV) COPD relative to age-matched non-COPD control subjects, which may be linked with altered smoking status and/or history (33). In these studies, we also observed that DUOX1 downregulation correlated significantly with loss of lung function and that DUOX1-deficiency worsened experimentally induced emphysema in mice (33). Hence, we believe that loss of DUOX1 with age (perhaps related to chronic exposure history to, e.g., tobacco smoke) may enhance the risk of COPD and may also contribute to lung function decline during "healthy" aging.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of tracheal and bronchial epithelium collected by airway brushing or laser capture micro-dissection, revealed that DUOX1 was significantly suppressed in the airways of healthy smokers and patients with COPD, when compared to age-matched control subjects, implying that chronic smoking leads to decreased airway epithelial expression of DUOX1 as a potential contributing factor in COPD development [ 216 , 217 ]. Our group expanded on these findings, by showing a gradual downregulation of DUOX1 protein in the small airways of GOLD II-IV COPD patients, which was found to be strongly correlated with various measures of lung function decline, and several markers of small airway remodeling and destruction [ 218 ]. On one hand, these results may imply that variable DUOX1 downregulation as a result of normal aging (see above) or smoking history may predispose for COPD development and progression.…”
Section: Nox Enzymes In Copd Pathologymentioning
confidence: 99%
“…Alternatively, it is also possible that DUOX1 downregulation may be a consequence of COPD, for example secondary to production of inflammatory mediators or growth factors such as TGF-β. Indeed, we observed that chronic exposure of bronchial epithelial cells to TGF-β also downregulates DUOX1 [ 218 ]. Downregulation of DUOX1 may be related to smoking history, although some studies suggest that exposure to CS extract can actually enhance DUOX1 expression [ 219 ].…”
Section: Nox Enzymes In Copd Pathologymentioning
confidence: 99%
See 1 more Smart Citation